Using Modular Construction Terms - Khokhrіakova D.O. (Ways to Improve Construction Efficiency, 2022)
With the growing number of international construction projects, the development of the international building materials market and the European integration of Ukraine, there is a growing need to harmonize common terminology in this area. When translating, new borrowed terms still have weak family ties in the new language, which means there is a high risk of inadequate use. The article is devoted to the analysis of terms and definitions related to modular construction in modern construction terminology for their further use in the harmonization of international standards and inclusion in explanatory dictionaries of construction terms. Terms such as prefab and modular construction refer to off-site or on-site prefabrication and process improvement, and refer to new borrowed terms. These terms require critical analysis, as they are usually used as synonyms, because designers and builders are not always aware of their difference, which causes a lot of confusion. To substantiate the terminology of modular construction, one should rely on the experience of leading specialized construction companies and the opinion of foreign scientists involved in research in this area. Triumph Modular advises considering "prefab" as a general term because it refers to prefabrication and is used in relation to anything that takes place off site. Moreover, panel sections (walls, roofs and floors), which significantly speed up the assembly at the construction site, it is appropriate to call prefab – structures, but not modules. The trade association Modular Building Institute suggests that the term "modules" refers to a special kind of prefabricated components that form a space, such as an entire room. The author also analyzed the relevant terms and definitions contained in the current regulations and guidelines of the UK – the world’s leading country in terms of the volume and pace of modular construction. Based on the results of the analysis of the harmonization of the terms of modular construction, it is proposed to carry out on the basis of the following statements: it is volumetric-block structural systems that should be considered modular; modular relate primarily to systems with a wooden and metal frame; modular construction is more capital construction.